Evaluation of phytoconstituents in marigold effluent for their antifungal activity against plant pathogens - Sanam, Tulja; Nagaraju, Umashankar; P. S, Benherlal; Nerella, Sridhar Goud; R, Jayaramaiah.; G. G, Kadalli.; V, Satya Srii. (Frontiers in Fungal Biology, 2024)
The current study placed an intense emphasis on the excess discharge of agro-based industrial effluent and the use of plant extract antimicrobials to inhibit the growth of pathogens in crop plants. An effluent (treated and untreated) from the marigold flower processing industry has been identified for the presence of volatile and semi-volatile organic compounds, and a total of 18 in treated effluent and 23 in untreated effluent were found using gas chromatography–mass spectrometry. A total of 13 classes were identified, which include carboxylic acid, phenols, esters, alkanes, alkenes, alcohols, cyanide, heterocyclic, flavonoids, aldehydes, polycyclic aromatic, cycloalkanes, and cycloalkenes. A principal component analysis with varimax rotation was applied to discern the abundance of identified compounds under each class. An in vitro antifungal bioassay was conducted using effluents at three different concentrations against plant pathogens (Alternaria alter nata, Sclerotium rolfsii, Rhizoctonia solani, Pythium aphanidermata, Fusarium oxysporum, and Colletotrichum gloeosporioides). The study proved that treated and untreated effluents clearly inhibited the growth of fungal pathogens by 10 to 32% and 37 to 92%, respectively. The findings suggest that marigold flower effluent can be a promising resource for developing new plant protection methods that are effective against pathogenic fungi.